1997
DOI: 10.1021/bi962410z
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide-Induced Stable Complex Formation by HIV-1 Reverse Transcriptase

Abstract: Nondenaturing gel electrophoresis was used to study the nucleotide substrate-induced conformational change in reverse transcriptase (RT) of human immunodeficiency virus type 1 (HIV-1). Dead-end complex was formed between HIV-1 RT, dideoxynucleotide chain-terminated primer, and DNA template in the presence of deoxynucleotide triphosphate (dNTP) complementary to the next position on the template. Complexes which form in the absence of the next complementary dNTP were disrupted by adding excess poly(rA)/oligo(dT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
121
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(127 citation statements)
references
References 50 publications
6
121
0
Order By: Relevance
“…Our previous site-specific footprinting experiments with stalled HIV-1 RT complexes revealed that the presence of the templated nucleotide can stabilize and trap the post-translocated complex (27). The next complementary nucleotide facilitates the formation of a stable ternary complex that blocks pyrophosphorolysis and the ATP-dependent excision of chain terminating nucleotides (15,29). Together, these observations are consistent with a Brownian ratchet model for polymerase translocation (36).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Our previous site-specific footprinting experiments with stalled HIV-1 RT complexes revealed that the presence of the templated nucleotide can stabilize and trap the post-translocated complex (27). The next complementary nucleotide facilitates the formation of a stable ternary complex that blocks pyrophosphorolysis and the ATP-dependent excision of chain terminating nucleotides (15,29). Together, these observations are consistent with a Brownian ratchet model for polymerase translocation (36).…”
Section: Discussionsupporting
confidence: 79%
“…Band shift experiments have revealed that binary complexes of HIV-1 RT and primer/template are unstable when challenged with a trap, e.g. heparin (29). However, the presence of dNTP substrate can stabilize the complex, which prevents dissociation in the presence of trap.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phosphorolytic cleavage of incorporated 2Ј,3Ј-dideoxynucleotides, including ddAMP and ddTMP, is compromised at nucleotide concentrations as low as 1 M, whereas significantly higher concentrations are required to inhibit the excision of AZT-MP. The formation of a stable ternary dead end complex is diminished with AZT-terminated primer strands, which provides an explanation for the efficient removal of AZT-MP (16).…”
mentioning
confidence: 99%